Maternal PM2.5 exposure triggers preterm birth: a cross-sectional study in Wuhan, China - Xiaotong Zhang; Cuifang Fan; Zhan Ren; Huan Feng; Shanshan Zuo; Jiayuan Hao; Jingling Liao; Yuliang Zou; Lu Ma (BMC, 2020)
Abstract Background Most of the studies regarding air pollution and preterm birth (PTB) in highly polluted areas have estimated the exposure level based on fixed-site monitoring. However, exposure assessment methods relying on monitors have the potential to cause exposure misclassification due to a lack of spatial variation. In this study, we utilized a land use regression (LUR) model to assess individual exposure, and explored the association between PM2.5 exposure during each time window and the risk of preterm birth in Wuhan city, China. Methods Information on 2101 singleton births, which were ≥ 20 weeks of gestation and born between November 1, 2013 and May 31, 2014; between January 1, 2015 and August 31, 2015, was obtained from the Obstetrics Department in one 3A hospital in Wuhan. Air quality index (AQI) data were accessed from the Wuhan Environmental Protection Bureau website. Individual exposure during pregnancy was assessed by LUR models and Kriging interpolation. Logistic regression analyses were conducted to determine the association between women exposure to PM2.5 and the risk of different subtypes of PTB. Results During the study period, the average individual exposure concentration of PM2.5 during the entire pregnancy was 84.54 μg/m3. A 10 μg/m3 increase of PM2.5 exposure in the first trimester (OR: 1.169; 95% CI: 1.077, 1.262), the second trimester (OR: 1.056; 95% CI: 1.015, 1.097), the third trimester (OR: 1.052; 95% CI: 1.002, 1.101), and the entire pregnancy (OR: 1.263; 95% CI: 1.158, 1.368) was significantly associated with an increased risk of PTB. For the PTB subgroup, the hazard of PM2.5 exposure during pregnancy was stronger for very preterm births (VPTB) than moderate preterm births (MPTB). The first trimester was the most susceptible exposure window. Moreover, women who had less than 9 years of education or who conceived during the cold season tended to be more susceptible to the PM2.5 exposure during pregnancy. Conclusions Maternal exposure to PM2.5 increased the risk of PTB, and this risk was stronger for VPTB than for MPTB, especially during the first trimester.